The critic of Romani music (Romanes) - Dužda, Jan (Romano džaniben, 2022)
A critical essay in which the author reflects on the development of Romani music, shifts and stagnations in its genres and song-writing. The author draws on his professional and personal experience as a musician, singer, member of a Romani music group, and Romani studies researcher. The essay is published in Romani without translation.